2013
DOI: 10.1074/jbc.m113.462291
|View full text |Cite
|
Sign up to set email alerts
|

Induction of a Tumor-associated Activating Mutation in Protein Tyrosine Phosphatase Ptpn11 (Shp2) Enhances Mitochondrial Metabolism, Leading to Oxidative Stress and Senescence

Abstract: Background:The pathogenic effects of tumor-associated activating mutations of Ptpn11 have not been well characterized. Results: Ptpn11E76K/ϩ mouse embryonic fibroblasts display increased ROS levels, cellular senescence, and enhanced mitochondrial respiration upon induction of the mutation. Conclusion: Induction of the Ptpn11E76K/ϩ mutation results in oxidative stress by enhancing mitochondrial metabolism. Significance: This study provides novel insights into the initial effects of Ptpn11-activating mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 50 publications
2
28
0
1
Order By: Relevance
“…In addition, we could determine that some markers of adipose tissue beiging were upregulated in adipose tissues from LS mice, notably in s.c. fat pads, suggesting that this adipose tissue has enhanced oxidative activity, which could contribute to enhanced energy expenditure. Interestingly, several studies have shown that SHP2 could regulate mitochondria activity, although the signaling pathways that link SHP2, and its LS-associated mutants, to the regulation of mitochondria function and energy homeostasis remain to be documented (37)(38)(39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we could determine that some markers of adipose tissue beiging were upregulated in adipose tissues from LS mice, notably in s.c. fat pads, suggesting that this adipose tissue has enhanced oxidative activity, which could contribute to enhanced energy expenditure. Interestingly, several studies have shown that SHP2 could regulate mitochondria activity, although the signaling pathways that link SHP2, and its LS-associated mutants, to the regulation of mitochondria function and energy homeostasis remain to be documented (37)(38)(39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…It should be borne in mind that their activity is significantly affected by changes in the redox status of the environment, oxidation enhancing their activity, in sharp contrast with tyrosine phosphatases (PTPs), which are inhibited by oxidative stress (Giannoni and Chiarugi 2014). Thus, high levels of ROS lead to elevated tyrosine phosphorylation, with potentially dramatic changes in mitochondrial function (Zheng et al 2013). Interestingly, SFKs are also keys to reducing ROS levels by phosphorylating a component of complex II of the respiratory chain, i.e., flotillin-1 (Ogura et al 2014), which again emphasizes the importance of this class of enzymes as both regulators and effectors in mitochondrial physiology.…”
Section: Tyrosine Phosphorylation Ros Polyamines and Mitochondriamentioning
confidence: 98%
“…It was demonstrated that low metastatic tumor cells have lower oxygen consumption than high metastatic tumors, including osteosarcoma. 30,31 Although many studies reported a shift from oxidative phosphorylation to glycolysis to provide energy for cellular activities in cancer cells, 32 cancer cells have also been reported to rely on oxidative phosphorylation and mitochondrial bioenergetics pathways for anabolism and energy production. 33 Our present finding indicates that PP2A Cα is involved in the regulation of mitochondrial respiratory capacity.…”
Section: Discussionmentioning
confidence: 99%